Exploratory Study on Customer Requirement in View of Electric Vehicle Development in Malaysia: Electric Vehicles in Malaysia (S/O: 12726) - Ibrahim, Jafni Azhan; Yusoff, Rushami Zien; Osman, Nor Hasni; Mohammed Udin, Zulkifli; Shariff, Kamal Imran; Ahmad, Azhar
Advancements in technology have developed rapidly until the emergence of new innovations that bring about huge benefits to humans. Similarly, technological advancements in the automotive field have always offered new inventions in the field of vehicle industry. Numerous innovations presented lead to greater comforts, enhanced safety and better ride quality. Recent advancement in the field of automotive technology is the presence of electric vehicles to market. The choice of electricity to power the vehicle of tomorrow is critical and large number of factors must be weighed. This choice needs to consider not only the advanced technology but also the safety and health considerations, overall infrastructure costs, fuel cost on a tax neutral basis and acceptance by the public. The main question is whether there is enough interest on the part of the government and vehicle customers to encourage the industry to commercialize this technology. The aim of this research is to analyze potential car buyers’ awareness towards electric vehicle (EV) and examine the factors that are most likely to affect their choice for EV in Malaysia. In maneuvering all resources towards achieving the research objectives, a Balanced Approach is believed to be the right strategy which can balance the tradeoff between control, realism and generalizability. For that, research activities will be conducted in two different stages in which are qualitative and quantitative approaches. The development of this instrument consists of five (5) main components: the level of access of vehicles, purchase of vehicles, the distance traveled, the awareness of electric vehicles and the purchase of cars in the future. The questionnaire was developed with three (3) main divisions, namely (1) the demographics of respondents, (2) knowledge of the vehicle in general, and (3) awareness of electric vehicles. From the results, it is found that the usage of electric vehicle is still very low, however, it has great potential in demand where most of the respondents show their desire to own electric vehicles in future.